The executioner's hand: the mental health impact of the LGBT + population after the 2018 election period in Brazil (Research, Society and Development, 2020)
The article aims to analyze the impact on the mental health of the LGBT + population, after the electoral period the 2018, correlating with the main facts that occurred in these three axes: subjectivity, politics and health. With a view to understanding the reflexes they caused due to stigmas, discrimination, prejudice, as well as the threat against their social and human rights, these conquered with great difficulty, during the electoral period. The methodology used for this work was a qualitative research, developed in the capital of Piauí, Teresina. The information was collected through semi-structured interviews and analyzed using the method of interpretation of meanings carried out with Lesbians, Gays, Bisexuals, Travestis and Transsexuals. (LGBT´s) regardless of whether they are assumed to be their relatives or not, aged 18 or over, members of a social movement on LGBT causes and who have already completed or are in higher education. The results show how the figure of Jair Bolsonaro contributed to legitimize a network of hate speech against “social minorities”, among them LGBT people, culminating in a necropolitics or politics of death.